Physical and Ecological Carrying Capacity for Cave Tourism Management - CHEABLAM, Onanong; RATTANARAT, Jantira (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021, 2021)
Cave tourism is a nature-based tourism which has recently gained its popularity in Thailand. Cave sare natural attractions which are extremely vulnerable, especially caves with limitations in both size and area. Thus, this study aims at studying and determining the maximum and suitable carrying capacity to support physical and ecological tourism in Ban Tham Sua tourism community area to avoid overtourism. The methodology used in this research was a survey on the tourist’s utilization, duration, number of tourists, and tourism impacts. Moreover, the impact assessment using 16 indicators presented by 5 geological experts for ecological carrying capacity of the cave areas were also conducted. This area-based study was conducted in 3 areas: Thep Nimit Cave, Nang Fa Cave, and Sua Noi Cave. The study found that the number of tourists in these three caves were below carrying capacitywhich had no or insignificant impact on natural resources. However, it was found that SuaNoi Cave was a huge destruction of the original resources. The study suggests that carrying capacity of cave tourism should be well planned and managed to prevent the environmental degradation.